Cluster Matarices for Industrial Occupations. Education for Employment Task Lists - Dimmlich, David; Lake County Area Vocational Center, Grayslake, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
These cluster matrices provide duties and tasks that form the basis of instructional content for secondary, postsecondary, and adult training programs industrial health occupations. The 14 clusters (and the job titles included in each cluster) are as follows: (1) construction (bricklayer, carpenter, building maintenance worker, electrician, maintenance painter, plumber/pipefitter); (2) electronic (computer repair technician, electrical and electronic technician); (3) graphic communications (commercial artists, compositors and/or typesetters, offset lithographic press operators, printing photographers, camera operators); (4) transportation (automotive mechanic, diesel mechanic, gasoline engine/mower repair); (5) manufacturing (machine tool operator, machinist, tool and die maker, punch press operator, sheet metal worker, combination welder, maintenance repairer, automated manufacturing systems technician, thermoplastic machine set-up specialist); (6) technical preparation (computer repair technician, electrical and electronic technician, automated manufacturing systems technician); (7) auto body repairer; (8) bus driver; (9) drafter/computer-aided drafter; (10) truck driver; (11) correction officers and jailers; (12) electric home appliance and power tool repairer; (13) office machine/cash register repairer; and (14) telephone and cable television line installers/repairers. (YLB)
Sponsoring Agency: Illinois State Board of Education, Springfield. Dept. of Adult, Vocational and Technical Education.
Contract Number: PS-10-130.
ERIC Note: For related task lists, see CE 058 970.
Educational level discussed: Adult Education.
Educational level discussed: Postsecondary Education.
Educational level discussed: Secondary Education.
Keywords: Adult Education; Appliance Repair; Auto Body Repairers; Auto Mechanics; Behavioral Objectives; Building Trades; Carpentry; Commercial Art; Computer Assisted Design; Construction (Process); Criminology; Drafting; Electricians; Electronic Technicians; Employment Potential; Equipment Maintenance; Graphic Arts; Industrial Education; Job Skills; Job Training; Machine Repairers; Machine Tool Operators; Machinists; Manufacturing; Masonry; Matrices; Occupational Clusters; Painting (Industrial Arts); Plumbing; Postsecondary Education; Printing; Secondary Education; Sheet Metal Work; Small Engine Mechanics; Task Analysis; Television Radio Repairers; Tool and Die Makers; Welding; Illinois; Bus Drivers -- Correctional Officers -- Truck Drivers; Guides, Classroom -- Teacher